The society of risk (Dimensión Empresarial, 2017)
Editorial written in relation to risk as a factor of change beyond the evolutionary paradigm.ResumenEditorial escrito en relación con el riesgo como factor de cambio mas allá del paradigma evolutivo.ResumoEditorial escrito em relação ao risco como fator de mudança além do paradigma evolutivo